Results from the UNITED study: a multicenter study validating the prognostic effect of the tumor–stroma ratio in colon cancer - Polack, M.; Smit, M.A.; van Pelt, G.W.; Roodvoets, A.G.H.; Meershoek-Klein Kranenbarg, E.; Putter, H.; Gelderblom, H.; Crobach, A.S.L.P.; Terpstra, V.; Petrushevska, G.; Gašljević, G.; Kjær-Frifeldt, S.; et al. (ESMO open, 2024)
The TNM (tumor–node–metastasis) Evaluation Committee of Union for International Cancer Control (UICC) and College of American Pathologists (CAP) recommended to prospectively validate the cost-effective and robust tumor–stroma ratio (TSR) as an independent prognostic parameter, since high intratumor stromal percentages have previously predicted poor patient-related outcomes. The ‘Uniform Noting for International application of Tumor-stroma ratio as Easy Diagnostic tool' (UNITED) study enrolled patients in 27 participating centers in 12 countries worldwide. The TSR, categorized as stroma-high (>50%) or stroma-low (≤50%), was scored through standardized microscopic assessment by certified pathologists, and effect on disease-free survival (DFS) was evaluated with 3-year median follow-up. Secondary endpoints were benefit assessment of adjuvant chemotherapy (ACT) and overall survival (OS). A total of 1537 patients were included, with 1388 eligible stage II/III patients curatively operated between 2015 and 2021. DFS was significantly shorter in stroma-high (n = 428) than in stroma-low patients (n = 960) (3-year rates 70% versus 83%; P < 0.001). In multivariate analysis, TSR remained an independent prognosticator for DFS (P < 0.001, hazard ratio 1.49, 95% confidence interval 1.17-1.90). As secondary outcome, DFS was also worse in stage II and III stroma-high patients despite adjuvant treatment (3-year rates stage II 73% versus 92% and stage III 66% versus 80%; P = 0.008 and P = 0.011, respectively). In stage II patients not receiving ACT (n = 322), the TSR outperformed the American Society of Clinical Oncology (ASCO) criteria in identifying patients at risk of events (event rate 21% versus 9%), with a higher discriminatory 3-year DFS rate (stroma-high 80% versus ASCO high risk 91%). A trend toward worse 5-year OS in stroma-high was noticeable (74% versus 83% stroma-low; P = 0.102). The multicenter UNITED study unequivocally validates the TSR as an independent prognosticator, confirming worse outcomes in stroma-high patients. The TSR improved current selection criteria for patients at risk of events, and stroma-high patients potentially experienced chemotherapy resistance. TSR implementation in pathology diagnostics and international guidelines is highly recommended as aid in personalized treatment. [Display omitted] •The TSR is a cost-effective and robust histological parameter scored on routine hematoxylin–eosin-stained slides.•This study prospectively validates the independent prognostic effect of the TSR for patients with stage II-III colon cancer.•Stroma-high tumors (i.e. intratumoral stromal percentage >50%) significantly lead to worse DFS.•Stroma-high tumors also exhibit chemotherapy resistance, emphasizing a clinical need for new therapy strategies.•Implementation of the TSR in international guidelines for improved guidance in oncological therapy selection is envisioned.